Genetic network analysis of human immunodeficiency virus sexual transmission in rural Southwest China after the expansion of antiretroviral therapy: A population-based study - Chen, Jin; Chen, Huanhuan; Li, Jianjun; Luo, Liuhong; Kang, Ruihua; Liang, Shujia; Zhu, Qiuying; Lu, Huaxiang; Zhu, Jinhui; Shen, Zhiyong; Feng, Yi; Liao, Lingjie; et al. (Frontiers in Microbiology, 2022)
Background: To analyse the genetic network of HIV sexual transmission in rural areas of Southwest China after expanding antiretroviral therapy (ART), and to investigate the factors associated with HIV sexual transmission through the genetic network. Methods: This was a longitudinal genetic network study in Guangxi, China. The baseline survey and follow-up study were conducted among HIV patients in 2015, and among newly diagnosed HIV patients from 2016 to 2018, respectively. A generalised estimating equation model was employed to explore factors associated with HIV transmission through genetic linkage between newly diagnosed HIV patients (2016-2018) and HIV patients at baseline (2015-2017), respectively. Results: Of 3,259 identified HIV patient sequences, 2,714 patients were at baseline and 545 were newly diagnosed HIV patients at follow-up. A total of 8,691 baseline objectives were observed by repeated measurement analysis. The prevention efficacy in HIV transmission for treated HIV patients was 39% [adjusted odds ratio (AOR): 0.61, 95% confidence interval (CI): 0.44-0.85]. Stratified analyses indicated the prevention efficacy in HIV transmission for treated HIV patients with viral load (VL) <50 copies/ml and HIV patients treated for four years with a VL <50 copies/ml to be 47 [AOR:0.53, 95%CI: 0.38-0.74] and 69% [AOR:0.31, 95%CI: 0.22-0.45], respectively. No significant reduction in HIV transmission occurred among treated HIV patients with VL missing or treated HIV patients on dropout. Some factors were associated with HIV transmission, including over 50 years old, male, Zhuang and other nationalities, less than secondary schooling, working as a farmer, and heterosexual transmission. Conclusion: This study reveals the role of ART in reducing HIV transmission, and that older male farmers with less than secondary schooling to be at high risk of HIV infection at a population level. Improvements to ART efficacy for HIV patients and precision intervention on high risk individuals during the expansion of ART are urgently required.